The Differential Impact of Acute Exercise and Mindfulness Meditation on Executive Functioning and Psycho-Emotional Well-Being in Children and Youth With ADHD - Bigelow, Hannah; Gottlieb, Marcus D.; Ogrodnik, Michelle; Graham, Jeffrey D.; Fenesi, Barbara (Frontiers in Psychology, 2021)
This study investigated how acute exercise and mindfulness meditation impacts executive functioning and psycho-emotional well-being in 16 children and youth with ADHD aged 10-14 (male=11; White=80%). Participants completed three interventions: 10 minutes of exercise, 10 minutes of mindfulness meditation, and 10 minutes of reading (control). Before and after each intervention, executive functioning (inhibitory control, working memory, task-switching) and psycho-emotional well-being (mood, self-efficacy) were assessed. Mindfulness meditation increased performance on all executive functioning tasks whereas the other interventions did not (d=0.55-0.86). Exercise enhanced positive mood and self-efficacy whereas the other interventions did not (d=0.22-0.35). This work provides preliminary evidence for how acute exercise and mindfulness meditation can support differential aspects of executive and psycho-emotional functioning among children and youth with ADHD.